Case Report: Nine-year-old with parathyroid adenoma within the piriform sinus - Zenno, Anna; Ramamoorthy, Bhavishya; Hammoud, Dima A.; Quezado, Martha; Zeiger, Martha A.; Jha, Smita (Frontiers in Endocrinology, 2023)
We present the case of a 9-year-old girl who presented with symptomatic hypercalcemia from primary hyperparathyroidism (PHPT). Laboratory results revealed elevated serum calcium 12.1 mg/dl (ref: 9.1–10.4), elevated ionized calcium 6.8 (ref: 4.5–5.6) mg/dl, phosphorus 3.8 (ref: 3.3–5.1) mg/dl, 25-OH vitamin D 20.1 (30–100) ng/ml, and elevated intact PTH 70 (15-65) pg/ml, consistent with the diagnosis of PHPT. She had persistent hyperparathyroidism after bilateral neck exploration, left thyroid lobectomy, and transcervical thymectomy. Neither inferior gland was identified. No parathyroid tissue was seen on histology. Repeat preoperative imaging identified a 7-mm × 5-mm adenoma on 4DCT not seen on 99Tc-sestamibi parathyroid scan. The patient then underwent a successful redo parathyroidectomy with removal of a submucosal left parathyroid adenoma at the superior aspect of the thyroid cartilage in the piriform sinus. Her biochemical work-up remains consistent with surgical cure 6 months after surgery. Herein, we also review common locations for ectopic parathyroid adenomas. Clinical Trial Registration NCT04969926.